Personal brand equity: Scale development and validation. Issue 3 (27th June 2020) - Gorbatov, Sergey; Khapova, Svetlana N.; Oostrom, Janneke K.; Lysova, Evgenia I.
Abstract: Crafting a personal brand has become an important factor for career success. Despite the growing literature on topics associated with personal brands, the conceptualization and measurement of personal brand equity (PBE) have received little attention. By drawing upon and integrating the marketing and careers literatures on branding, we reconceptualized the definition of PBE and delineated its dimensions and conceptual boundaries. Furthermore, we developed a 12‐item scale to measure PBE. Among seven different samples (total N  = 3, 273), including two samples of employees, this study tested the construct and criterion‐related validity of the PBE scale. First, exploratory and confirmatory factor analyses supported a three‐dimensional structure of PBE (brand appeal, brand differentiation, and brand recognition). In two samples, the convergent and discriminant validity of the PBE scale was established. Finally, this study showed that PBE predicts perceived employability, career success, and job performance. The PBE scale offers new opportunities to understand and measure career behaviors by considering individuals' personal brand positioning.